Analisis Yuridis Peraturan Menteri Keuangan Nomor 23 Tahun 2026 terhadap Penunggak Piutang Negara - Duma Hutapea; Rio Christiawan (Jurnal Hukum Lex Generalis, 2026)
The Ministry of Finance issued Minister of Finance Regulation (PMK) Number 23 of 2026 which revises PMK Number 240 of 2016, and is effective from April 24, 2026.” The issuance of PMK Number 23 of 2026 as an amendment to the provisions for the management of state receivables shows the government's efforts to strengthen the effectiveness of the settlement of state receivables through the mechanism of “the State Receivables Affairs Committee (PUPN).” The focus of this research is the changes in PMK Number 23 of 2026. The research method used is normative juridical or legislative approach. The purpose of this study is to further analyze the legal changes in PMK Number 23 of 2026.